P12-18 Countdown to 2027 – maximising the use of NAMs for food safety assessment: closing the gap for regulatory assessments in Europe - Wood, A.; Atienzar, F.; Basili, D.; Coulet, M.; Fernandez, R.; Galano, M.; Marin-Kuan, M.; Montoya, G.; Piechota, S.; Punt, A.; Reale, E.; Wang, S.; et al. (Toxicology letters, 2025)
An increasing number of New Approach/Non-Animal Methodologies (NAMs) has been developed over the years, with the aim to provide more informative, more efficient and more ethical risk assessments. This evolution in safety assessment strategies is also observed in the food sector, with a growing effort to move away from animal testing. The ambition of the European Food Safety Authority (EFSA) is to integrate the use of NAMs into risk assessments of regulated food products by 2027, leading to “the minimisation of animal testing”. Despite this objective, the use of NAMs remains limited in EU food evaluations and animal studies are still being requested for regulated food products. To address this, we review several NAMs relevant for food safety assessment and reflect on their presence in EU food safety regulation and sectoral guidance. We also suggest amendments to the EU food regulatory environment and propose potential research activities that could support the broader implementation of such NAMs. Fourteen NAMs of relevance to food safety are categorised based on: 1. the potential to inform hazard, exposure or risk, 2. their assessment domain, i.e. biological and chemical, and 3. the history of use of such methods, e.g. long standing and innovative method. These NAMs are: in silico methods, exposure-based waiving, read-across, genotoxicity testing, safe strain lineage, history of safe use, omics technologies, cellular stress pathways, pharmacological profiling, phenotypic profiling, adverse outcome pathways, approaches to assess allergenicity and toxigenicity, tools and approaches for ADME characterisation and integrated approaches to testing and assessment (IATA) combining several NAMs to support risk assessment. The presence of such NAMs in EU foods regulations and sector-specific guidelines is reviewed for a diverse range of regulated products. Sectoral guidance has recently been updated in the EU for many areas of regulated products. Most of them stress the general 3Rs principles and some guidance documents mention the potential use of specific NAMs, such as in silico approaches or exposure-based waiving, which is a significant progress. On the other hand, some NAMs are still entirely absent from the EU foods guidance and regulation, and certain sector-specific guidelines, such as those for food additives, still require the inclusion of animal studies. In addition, the explicit request for a qualification and validation of alternative approaches is believed to be a major limiting factor for their potential use to support a safety assessment. Several revisions of existing guidance are suggested in order to maximize the implementation of NAMs in food safety evaluation, including the proposal that animal testing should only be conducted “as a last resort”. For those NAMs not reflected in EU foods guidance, several research activities are required to build confidence and thereby enhance their use.